(untitled) (PERcursos Linguísticos, 2020)
In the present work, we assume that fantastic literature seems to be free of realistic conventions of representation of time, space, character, inanimate objects, me and the other. Furthermore, one of its thematic guidelines is the pursuit of what has been silenced, made invisible in the culture of official life (JACKSON, 2009). For this reason, it is intended, in this work, to investigate the representation of the magic body in the enunciated of dystopian fantasy, a hybrid genre that brings the existence of the supernatural in the midst of an authoritarian government in a world similar to ours, as a metaphor for discursive representations of marginalized bodies and oppressed people present in official life. In light of this, in order to achieve our objective, we first copulate/collate texts about the representation of marginalized bodies (LOURO, 2004), about the discursive representation of the body in aesthetic enunciateds (BAKHTIN, 2011) and also about the specific discursive representations of the fantasy genre (JACKSON, 2009) and, secondly, we present an analysis that puts the representation of these bodies in dialogue on the book Bone Season, by the english author Samantha Shannon.